Perencanaan PLTS Rooftop pada Wisata Pulau Gusung Toraja - Yunus, Esty Yunus; Taufiq Enri Rahman , Muhammad; ade, Adeaksa Samsul; Yunus, A.M. Shiddiq; Musrady Mulyadi (Jurnal Teknik Mesin Sinergi, 2025)
This study aims to determine the capacity of rooftop solar power plants to meet electricity needs on Gusung Toraja Island, design appropriate technical designs, and analyze the technical, economic, and environmental feasibility of the project. The method used is quantitative research with modeling using PVsyst, AutoCAD, and SketchUp software. Data were collected through interviews and observations. The design results show a power capacity of 5 kWp, energy production of 7,842 kWh/year, and an initial investment cost of IDR 197,117,200. Economic analysis shows an NPV of IDR 313,256,802 and a payback period of 15 years and 4 months, with an annual energy cost of IDR 3,714/kWh. PV system simulation produces an energy cost of IDR 1,296/kWh, an NPV of IDR 196,859,802, and a payback period of 12.2 years. With a positive NPV, a payback period shorter than the project life, a Profitability Index (PI) of 1.6, and an IRR higher than the interest rate, this investment is declared feasible and sustainable.